Effect of carboxymethylcellulose sodium addition as stabilizer for physicochemical characteristic of purple sweet potato fortified yogurt (Ipomoea batatas L.) - Uci Ary Lantika; Fitrianti Darusman; Widad Aghnia Shalannandia; Astrid Feinisa Khairani (Universitas Ahmad Dahlan, 2021)
The yoghurt consisted of low-fat milk, three bacterial strains starter, which included: L. bulgaricus ATCC 11842, L. plantarum ATCC 8014, and B. longum (1:1:1); purple sweet potato puree (Ipomoea batatas, L.) and carboxymethylcellulose sodium with the concentration of 0.6%, 1.2%, and 1.8%. Purple sweet potato fortification in yogurt can prevent hypercholesterolemic conditions because it inhibits lipid and sugar absorption in the intestine. Unfortunately, there is one shortcoming in the production of yogurt which affects the final product quality. This shortcoming is in the decrease in the air holding capacity (whey off) during the production due to the pH level within the isoelectric point of casein. This causes precipitation and phase separation. This study will add a stabilizer to the formula to overcome it. The stabilizer used is carboxymethylcellulose sodium, which is semi-synthetic water-soluble ester polymer cellulose. This study aimed to determine the optimal concentration of carboxymethylcellulose sodium and its effect on purple sweet potato yogurt's physicochemical and organoleptic properties. The product quality evaluations were on organoleptic evaluation, density, viscosity, and pH level. Centrifugation and freeze-thaw tests were also performed to evaluate product stability. The results showed that carboxymethylcellulose sodium could maintain the stability of purple sweet potato yogurt by binding the air content, increasing consistency, and smoothing the texture even though it did not affect the freezing point of the product. This study gave the best results for purple sweet potato yogurt with 1.2% carboxymethylcellulose sodium concentration.